2022
DOI: 10.3390/ph15040393
|View full text |Cite
|
Sign up to set email alerts
|

Antibiotic Resistance in the Drinking Water: Old and New Strategies to Remove Antibiotics, Resistant Bacteria, and Resistance Genes

Abstract: Bacterial resistance is a naturally occurring process. However, bacterial antibiotic resistance has emerged as a major public health problem in recent years. The accumulation of antibiotics in the environment, including in wastewaters and drinking water, has contributed to the development of antibiotic resistant bacteria and the dissemination of antibiotic resistance genes (ARGs). Such can be justified by the growing consumption of antibiotics and their inadequate elimination. The conventional water treatments… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(17 citation statements)
references
References 154 publications
0
12
0
Order By: Relevance
“…The production and consumption of antibiotics continue to increase worldwide because of their increased uses in human health as well as in medical care and disease prevention in livestock and aquaculture . After their administration, most antibiotics are not completely metabolized, and the undegraded antibiotics are excreted through urine and feces and ultimately enter aquatic environments. , The occurrence of antibiotics in the environment has caused public health concerns because elevated antibiotics in the environment induce antibiotic resistant bacteria and genes. In the past two decades, various physical treatment methods, e.g., activated carbon filtration and membrane technology, and chemical oxidation processes, e.g., chlorine, chlorine dioxide, ozonation, Fenton and Fenton-like processes, UV photolysis, and photocatalysis, have been applied to remove antibiotics from water. , Physical treatments only concentrate antibiotics without their transformation. Thus, advanced oxidation processes (AOPs) may be preferable because they have the potential to break down and even mineralize antibiotics.…”
Section: Introductionmentioning
confidence: 99%
“…The production and consumption of antibiotics continue to increase worldwide because of their increased uses in human health as well as in medical care and disease prevention in livestock and aquaculture . After their administration, most antibiotics are not completely metabolized, and the undegraded antibiotics are excreted through urine and feces and ultimately enter aquatic environments. , The occurrence of antibiotics in the environment has caused public health concerns because elevated antibiotics in the environment induce antibiotic resistant bacteria and genes. In the past two decades, various physical treatment methods, e.g., activated carbon filtration and membrane technology, and chemical oxidation processes, e.g., chlorine, chlorine dioxide, ozonation, Fenton and Fenton-like processes, UV photolysis, and photocatalysis, have been applied to remove antibiotics from water. , Physical treatments only concentrate antibiotics without their transformation. Thus, advanced oxidation processes (AOPs) may be preferable because they have the potential to break down and even mineralize antibiotics.…”
Section: Introductionmentioning
confidence: 99%
“…Intrinsic antibiotic resistance and acquired antibiotic resistance are also known [29] . The acquired resistance mechanisms also include modification of antibiotic targets by genetic mutation or post-translational modification of the target [29][30][31] . Various antibiotic resistance mechanisms and may vary with respect to the considered cells strains and antibiotic.…”
Section: Discussion 41 Antibiotic Resistant Bacillus Strains In Wells...mentioning
confidence: 99%
“…It has been indicated that the accumulation of antibiotics in the environment, including wastewaters and drinking water, can contributed to the development of antibiotic resistant bacteria and the dissemination of ARGs. It has been indicated that ARGs can temporary be transferred horizontally to other microorganisms within the atmosphere or aquatic environment, thus promoting the dissemination of antibiotic resistance [29] . For rainwater, the temporal variation of the antibiotic susceptibility of the Bacillus isolated strains could be related to meteorological factors such as wind and lightning.…”
Section: Variation Of the Antibacterial Susceptibility With The Seaso...mentioning
confidence: 99%
“…[4][5][6][7][8][9][10][11][12] In addition, the wide application of pharmaceuticals in daily life for the treatment of complex diseases is also the major contributor of emerging contaminants, with potential adverse effects on humans and the aquatic environment. [13][14][15][16][17][18][19][20][21][22] The presence of these pharmaceutical pollutants could lead to cancers, severe bleeding, organ damage, birth defects, reproductive disorders, endocrine disorders, and mild to severe toxic effects in human beings in the global population. 14 The toxic effects are also threats to mammals, other organisms, and the ecosystem.…”
Section: Introductionmentioning
confidence: 99%